2018
DOI: 10.1111/pde.13402
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and nail clippings in 52 children with psoriasis

Abstract: There seems to be a correlation between some microscopic nail features in children with psoriasis and their PASI and NAPSI scores, so nail clippings from children with suspected psoriasis may help with diagnosis, especially in the presence of neutrophils, and in excluding onychomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
8
0
4
Order By: Relevance
“…Recently, the use of nail clipping microscopy as a diagnostic tool for nail psoriasis has also been studied . Although there are many studies delineating the clinical features of nail psoriasis, very few have described the histopathological features, or tried to correlate the two.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the use of nail clipping microscopy as a diagnostic tool for nail psoriasis has also been studied . Although there are many studies delineating the clinical features of nail psoriasis, very few have described the histopathological features, or tried to correlate the two.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Recently, the use of nail clipping microscopy as a diagnostic tool for nail psoriasis has also been studied. [12][13][14][15] Although there are many studies delineating the clinical features of nail psoriasis, very few have described the histopathological features, or tried to correlate the two. In an attempt to bridge this gap, this descriptive cross-sectional study was undertaken to study the histopathological features of nail psoriasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Onychomycosis is classified into five different types depending on the invaded location: distal lateral subungual, white superficial, proximal subungual, endonyx and total dystrophic. Uber et al . suggested that the presence of nondermatophyte onychomycosis in patients with psoriasis is combined with pitting and salmon patches on the nail.…”
Section: Discussionmentioning
confidence: 97%
“…Onychomycosis is classified into five different types depending on the invaded location: distal lateral subungual, white superficial, proximal subungual, endonyx and total dystrophic. Uber et al 9 suggested that the presence of nondermatophyte onychomycosis in patients with psoriasis is combined with pitting and salmon patches on the nail. Having the hands constantly immersed in water can predispose to the development of chronic paronychia, resulting in poor nail growth, 10 infection with Pseudomonas aeruginosa 11 or onycholysis.…”
Section: Discussionmentioning
confidence: 99%